No hunger in my home - Brink, Nancy; Bagby, Rachel ([S.l.] : Department of Communication, Stanford University ; Kuala Lumpur : Visual Resources [distributed by], 1989)
Story about twenty million people are hungry in America. For many, it is the first time they have lacked funds for food. As the problem grows, local communities have been forced to care for people in need
Cinematographer, Tina Difellciantonio ; camera, Frances Reid ; music, Russel Walder...[et al.]
Keywords: Hunger -- California; Starvation